2023
DOI: 10.1126/scisignal.add0645
|View full text |Cite
|
Sign up to set email alerts
|

IHH, SHH, and primary cilia mediate epithelial-stromal cross-talk during decidualization in mice

Abstract: The establishment of pregnancy depends on interactions between the epithelial and stromal cells of the endometrium that drive the decidual reaction that remodels the stroma and enables embryo implantation. Decidualization in mice also depends on ovarian hormones and the presence of a blastocyst. Hedgehog signaling is transduced by primary cilia in many tissues and is involved in epithelial-stromal cross-talk during decidualization. We found that primary cilia on mouse uterine stromal cells increased in number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…1). Li et al 50 found that blastocyst-derived TNFα induces epithelial IHH, which stimulates expression of SHH in the stroma and thereby augments decidualization. Chen et al 51 further discovered that TNFα produced by the embryo promotes release of arachidonic acid from the epithelium to ignite fibroblast activation and decidualization through PGI2 and PPARδ.…”
Section: In Micementioning
confidence: 99%
See 1 more Smart Citation
“…1). Li et al 50 found that blastocyst-derived TNFα induces epithelial IHH, which stimulates expression of SHH in the stroma and thereby augments decidualization. Chen et al 51 further discovered that TNFα produced by the embryo promotes release of arachidonic acid from the epithelium to ignite fibroblast activation and decidualization through PGI2 and PPARδ.…”
Section: In Micementioning
confidence: 99%
“…1). Li et al 50 . found that blastocyst-derived TNFα induces epithelial IHH, which stimulates expression of SHH in the stroma and thereby augments decidualization.…”
Section: Recent Progress In Endometrial-decidual Transformation Resea...mentioning
confidence: 99%
“…Research has demonstrated the presence of primary cilia in human endometrial stromal cells. Within stromal cells, Sonic Hedgehog (SHH) stimulates the canonical Hedgehog (Hh) signaling pathway via primary cilia and facilitates decidualization through mechanisms implicating interleukin-11 (IL-11) and primary cilia ( Li et al, 2023 ). Mounting evidence suggests that impaired decidualization is closely associated with Recurrent Implantation Failure (RIF).…”
Section: Primary Cilia and Reproductive System-related Disordersmentioning
confidence: 99%